Exploration of Elementary School Teachers' Competencies in the Integration of Technology in Classroom Learning Practices: Gioia Method-Based Qualitative Study - Frinco Yulens Wurung; Mita Rahayu; Reginaldus Patrio; Edilinda Clauni; Siti Ni'matul Fitriyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Technology integration in primary education has become an essential aspect of improving learning quality and preparing students for the demands of the digital era. However, successful technology integration depends not only on the availability of digital resources but also on teachers’ competencies and the contextual factors that influence their implementation practices. This study aimed to explore primary school teachers’ competencies in integrating technology into classroom practice and to identify the factors influencing technology integration in primary education. A qualitative exploratory approach was employed, involving 15 participants consisting of primary school teachers from different generations, school principals, and school supervisors selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the Gioia methodology, which involved developing first-order concepts, second-order themes, and aggregate dimensions. The findings revealed four dimensions of teacher competencies in technology integration: pedagogical competence, social competence, professional competence, and attitudes toward technology. These dimensions illustrate that technology integration extends beyond technical skills to encompass the ability to use technology for teaching, communication, professional development, and continuous adaptation to technological change. The study also identified three contextual factors influencing technology integration, namely institutional support, implementation barriers, and strategies for professional development. Institutional support, such as technological facilities and continuous training, facilitated technology integration, whereas limited resources, varying levels of teacher readiness, and resistance to change emerged as major challenges. In conclusion, effective technology integration in primary education requires not only multidimensional teacher competencies but also supportive educational ecosystems characterized by adequate technological infrastructure, sustained professional development opportunities, institutional support, and collaboration among schools, educational authorities, and higher education institutions to foster continuous professional learning and digital transformation.